Patient's willingness to opt for external cephalic version. (March 2013) - Vlemmix, Floortje; Kuitert, Marjon; Bais, Joke; Opmeer, Brent; van der Post, Joris; Mol, Ben Willem; Kok, Marjolein
Abstract: Objective : External cephalic version (ECV) is a relatively simple and safe maneuver that reduces the cesarean section (CS) rate for breech presentation. There is professional consensus that ECV should be offered to all women, but only up to 70% of patients opt for this treatment. To improve counseling, we investigated the value patients place on various aspects of ECV. Methods : We studied patient preferences by means of a vignette study. Varying levels of treatment characteristics were investigated in 16 scenarios, all including the "opt out" alternative of an elective CS. The probability that women preferred ECV was estimated using a logistic regression approach. Results : Forty seven women participated in the study. Pain was the most important factor negatively influencing the willingness to opt for ECV (OR 0.11 (95% confidence interval (CI) 0.05–0.23) for a pain score of 8–10 compared to 1–2 on a visual analog scale of 0–10). Higher success rates of vaginal delivery after successful ECV increased women's willingness (OR 3.42 (95% CI 2.04–5.74), if chance of vaginal delivery after successful ECV increased from 24% to 52%). The risk of an emergency CS during ECV did not influence the willingness to opt for ECV (OR 0.83 (95% CI 0.59–1.18) of chance increased from 0% to 1%). Conclusions : We conclude that expected pain during treatment and the success rate are the most important factors influencing the willingness to undergo ECV. Taking this information into account when counseling for ECV and reassuring women that unbearable pain is always a reason to stop ECV, and that the vast majority of women reported that the experienced pain is bearable, might improve the uptake of ECV and decrease the number of CS due to breech presentation.